Evaluación de la gestión de seguridad y salud ocupacional en la empresa APRONAM S.A del cantón Chone - Cepeda Paucar, Janneth Marisol (2020)
The objective of the investigation carried out was to evaluate the Occupational Health and Safety Management (GSSO) for the reduction of occupational risks in the company APRONAM S.A in the canton of Chone. For its compliance, a three-phase methodology was developed: firstly, the regulations of the GSSO System were identified through bibliographic review, for subsequent analysis and comparison with the information included in the Internal Regulations of Hygiene and Safety; as a second point, the current situation of the company was determined through the application of an interview to management, a survey of each of the 33 employees and an observation sheet in the labor field, these instruments were validated with the method Delphi to give greater support to the evaluation, then the information obtained was tabulated and analyzed, and the existing risks for each work area were estimated using the triple criteria matrix, giving way to the determination of the existing problems using the Ishikawa Diagram, and prioritizing them through the Pareto Diagram; finally, the proposal for actions to improve the GSSO System to reduce occupational risks was prepared and socialized. The results of the investigation establish that the company complies with the regulatory requirements, however, the risks found are determined to be moderate and significant, and there is no evidence of periodic and continuous evaluations that provide an information base for proper decision-making regarding to the necessary improvements.